Methods and instrumentation for the investigation of groundwater systems (Paises Bajos | PAISES BAJOS Organization for Applied Scientific Research / The Netherlands, 1983)
The purpose of the symposium is to survey the recent development of the methods and instruments suitable for the determination of the parameters characterizing the groundwater systems. This introductory paper summarizes some principles, which should be considered and raises some questions, which should be answered when the most appropriate methods of groundwater studies are investigated.
Sin Especificar
Keywords: Aguas subterráneas-Métodos